2014
DOI: 10.1097/jto.0000000000000022
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mutations: Effect on Volume Doubling Time of Non–Small-Cell Lung Cancer Patients

Abstract: In NSCLC patients, positive EGFR mutation status may be associated with longer VDT, which seemed to have a slowly progressive and less-aggressive character. More accurate evaluation of VDT may be helpful for understanding the natural history of EGFR mutation-positive NSCLC and treatment with EGFR tyrosine kinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…This is supported by a previous investigation of the volume doubling time (VDT) in incidentally detected symptom-free NSCLC. In the study, the VDT in the 33 adenocarcinoma patients with EGFR mutations was longer than that in 36 adenocarcinoma patients with wild-type EGFR (676 vs. 200 days; P = 0.014) [28]. Several studies have suggested that lung cancer with a VDT of more than 400 days indicates an indolent tumor [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a previous investigation of the volume doubling time (VDT) in incidentally detected symptom-free NSCLC. In the study, the VDT in the 33 adenocarcinoma patients with EGFR mutations was longer than that in 36 adenocarcinoma patients with wild-type EGFR (676 vs. 200 days; P = 0.014) [28]. Several studies have suggested that lung cancer with a VDT of more than 400 days indicates an indolent tumor [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“… 7 A recent epidemiology study of EGFR mutations in Asian patients with advanced NSCLC showed that the mutation frequency was 43% in Asian patients, 52% of those being Chinese patients. 8 Most recently, Nakamura et al 9 reported that positive EGFR mutation status may be associated with longer volume doubling time in NSCLC patients. In our study, we found that P-LC patients have significant higher incidence of EGFR mutations, independent of sex, histological type, and smoking history.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al (12) firstly studied the relationship between VDT and EGFR mutation by retrospectively reviewing 102 NSCLCs and found that the VDTs of patients with EGFR mutations (median 676 days) were longer than those without EGFR mutations (median 139 days).…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al firstly described the possible relationships between VDT and EGFR mutation status, finding positive EGFR mutation status may be associated with longer VDT. However, the major limitation of Nakamura's study is the VDT calculation depended on conventional measurement methods and possible statistical bias could have been caused by squamous-cell carcinoma (12).…”
Section: Introductionmentioning
confidence: 99%